Identifikasi Cekaman Abiotik Varietas Jagung akibat Pemberian Bahan Organik Jerami padi dan Biochar pada Tanah Ultisol - Bukhari Bukhari; Jamilah Jamilah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2023)
Abiotic stress is a limiting factor in maize production on Ultisols. One solution that can be done to overcome this problem is through the selection of resistant corn varieties and by using organic matter as an amendment. The experiment tested the effect of abiotic stress on the growth of maize in Ultisols. Abiotic stress consisted of 10 (ten) treatments, namely: C0 (without drought stress/75% FC ), C1 (drought stress/37.5% FC), C2 (without phosphorus stress), C3 (phosphorus stress/ without phosphorus), C4 (without potassium stress), C5 (potassium stress/without potassium), C6 (without magnesium stress), and C7 (magnesium stress/ without magnesium), C8 (given organic matter) and C9 (without organic matter). The observed variables were the number of stomata, total chlorophyll content, cob dry weight, root dry weight, shoot dry weight, and plant biomass weight. The results showed that maize varieties had different response abilities to deficiencies of the three macronutrients. This is proven by the fact that there is a difference in the ability of corn to be stressed by the three nutrients, namely P, K and Mg. Corn that has the best adaptability is the Anoman I variety, this variety has the highest number of stomata and total chlorophyll, and the heaviest biomass, while the variety that has the lowest adaptability to nutrient deficiencies because it shows low responses to all the agrophysological characters above is the Lamuru variety. This identification shows that the Anoman 1 variety is the most resistant to nutrient stress while Lamuru is the most sensitive variety. Organic materials can increase the adaptability of corn to water and nutrient deficiencies. This fact can be seen from the results of research where the Lamuru variety which is sensitive to water and nutrient shortages can increase its adaptability after obtaining organic amendments of rice straw and biochar. In general, it can be concluded that abiotic stress, both water stress and nutrient stress (P, K, and Mg) affected all observed variables and there was a significant interaction between varietal differences and abiotic stress in Ultisols.Key Woard : Corn Varieties, Organic Amendment, Nutrition Stress Ultisol Soil and Water Stress